(untitled) (Journal of Psychiatrists’ Association of Nepal, 2026)
Introduction Doctors experiencing burnout are reported to be at a higher risk of making poor decisions; display hostile attitude toward patients; make more medical errors; and have difficult relationships with co-workers. Burnout among doctors also increases risk of depression; anxiety; sleep disturbances; fatigue; alcohol and drug misuse; marital dysfunction; premature retirement and perhaps most seriously suicide. This study aimed to determine the prevalence and levels of burnout among resident doctors using the Copenhagen Burnout Inventory and to examine its distribution across selected demographic and work-related characteristics. Methods A cross-sectional study was conducted among 63 resident doctors at Pokhara Academy of Health Sciences using a self-structured proforma for demographic data and the Copenhagen Burnout Inventory (CBI) to assess burnout across three domains: Personal, Work-Related, and Client-Related Burnout. Data were analyzed using descriptive statistics. Results The mean scores indicated moderate to high levels of burnout across all domains. The Work-Related Burnout domain scored the highest (mean score 66.9%), followed by Personal Burnout ( 63.2%) and Client-Relat- ed Burnout ( 49.4%). High weekly working hours (often exceeding 100 hours), numerous night duties, and unsatisfactory stipends were common among participants. Subgroup analysis suggested higher burnout levels in certain specialties like Obstetrics & Gynecology and Surgery, and among those who had faced workplace violence. Conclusion Burnout is a significant issue among resident doctors at PoAHS, with work-related factors being a primary contributor. The findings underscore the urgent need for systemic interventions, including workload management, improved stipends, and the establishment of robust mental health support systems within medical training institutions to safeguard the well-being of future physicians.